Invincible : ultimate collection. Volume 4 - Kirkman, Robert (Image Comics, 2009)
"No longer just the boy whose father tried to take over the world, Mark Grayson, Invincible-- is working his way up the pecking order on his way to becoming the premiere super-hero in the world. Super-villains, technologically reanimated super-corpses and alien invasions are only a few of the things Invincible must face in this non-stop thrill ride--"--Page [4] of jacket.